STRATEGI PERANG GERILYA ISIS DI IRAK PERIODE 2014-2015 - Wahyu Hidayat; Tri Cahyo Utomo; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This thesis discusses the success and solution of guerilla warfare strategy used by ISIS in Iraq between 2014 – 2015. By June 2014, ISIS had already occupied and took control of 30 cities in Iraq in just 19 days. The great expansion of ISIS continued until the following year of 2015. But at September 10th, 2014 when Barrack Obama, the President of the United States, announced the formation of international coalition to fight against ISIS, ISIS’s occupation area decreased by 14% to only 78.000 km2. The goal of this research is to capture and understand ISIS’s strategy to effectively practiced guerilla warfare and to see the efforts made by the international comunity especially members of the international coalition that was led by the United States. This research used qualitative method in which the author try to find answers to the success of ISIS’s war strategy that was done fast and effective in Iraq between 2014-2015. The result derived from this research is ISIS implemented theory of guerilla warfare strategy into politics, propagandas, military capability, financial sources, ideologies, government forms, and attacks or offensive.